COVID‐19, physical (in‐)activity, and dementia prevention - Müller, Patrick (Alzheimers Dement (N Y), 2020)
Physical inactivity is one major modifiable risk factor for dementia (especially Alzheimer's disease). Due to contact restrictions and isolation measures in response to the current COVID‐19 (coronavirus disease 2019) pandemic, physical inactivity levels have increased by up to 30%, which will likely have adverse consequences for primary and secondary dementia prevention. Therefore, new interdisciplinary prevention approaches (eg, outdoor exercise; app‐based exercise with online partners) are urgently needed that account for the suspected long‐term lifestyle changes that the current—and upcoming—pandemics are likely to entail (increased use of home office, social isolation, avoidance of fitness centers and club sports, and so on).